On charged black holes in 4D Lovelock theory coupled to ModMax nonlinear electrodynamics - Amirabi, Z. (Academic Press Inc Elsevier Science, 2022)
The ModMax nonlinear electrodynamics is a recently proposed model which possesses maximally symmetries among the well-known nonlinear electrodynamics models. This model consists of both Maxwell's invariants such that in the absence of either the electric or the magnetic field the model automatically reduces to the Maxwell linear theory. The presence of both scalar invariants which are necessary for the symmetries of the model makes it very special such that cannot be employed in higher or lower dimensions. Unfortunately, we observed in the literature that, this model has been applied in higher d-dimensions. This is still an early time for this model, however, it is becoming popular. We aim to clarify this specific important point by giving the correct approach to the 4D Einstein-Gauss-Bonnet gravity as well as 4D Einstein p-order Lovelock theory coupled to ModMax nonlinear electrodynamics. (C) 2022 Elsevier Inc. All rights reserved.
Keywords: ModMax; 3+1-dimensions; Gauss-Bonnet; Lovelock; Nonlinearelectrodynamics; Blackhole